Glycosides from Stevia rebaudiana Bertoni Possess Insulin-Mimetic and Antioxidant Activities in Rat Cardiac Fibroblasts. (30th August 2017) - Prata, Cecilia; Zambonin, Laura; Rizzo, Benedetta; Maraldi, Tullia; Angeloni, Cristina; Vieceli Dalla Sega, Francesco; Fiorentini, Diana; Hrelia, Silvana
Abstract : Stevia rebaudiana Bertoni is a shrub having a high content of sweet diterpenoid glycosides in its leaves, mainly stevioside and rebaudioside A, which are used as noncaloric, natural sweeteners. The aim of this study was to deepen the knowledge about the insulin-mimetic effect exerted by four different mixtures of steviol glycosides, rich in stevioside and rebaudioside A, in neonatal rat cardiac fibroblasts. The potential antioxidant activity of these steviol glycosides was also assessed, as oxidative stress is associated with diabetes. Likewise the insulin effect, steviol glycosides caused an increase in glucose uptake into rat fibroblasts by activating the PI3K/Akt pathway, thus inducing Glut4 translocation to the plasma membrane. The presence of S961, an insulin antagonist, completely abolished these effects, allowing to hypothesize that steviol glycosides could act as ligands of the same receptor engaged by insulin. Moreover, steviol glycosides counteracted oxidative stress by increasing reduced glutathione intracellular levels and upregulating expression and activity of the two antioxidant enzymes superoxide dismutase and catalase. The present work unravels the insulin-mimetic effect and the antioxidant property exerted by steviol glycosides, suggesting their potential beneficial role in the cotreatment of diabetes and in health maintenance.